Iodofluorination of Alkenes Using IF5–Pyridine–HF - Yano, Shohei; Hara, Shoji (Synthesis, 2015)
Iodofluorination of alkenes was performed by using IF5–pyridine–HF and a reductant such as potassium iodide or tin powder. The addition of IF to the double bond proceeded with stereo- and regioselectivity. In the reaction with internal alkenes, the trans-addition product was obtained selectively. With terminal alkenes, the addition took place regioselectively to give 1-iodo-2-fluoroalkanes.
Keywords: fluorine; addition; stereoselective synthesis; halogenation; alkenes